Point of Care Transesophageal Echocardiogram-Guided CPR - Yannis Amador (POCUS Journal)
During cardiopulmonary resuscitation (CPR), chest compressions are critical for augmenting cardiac output, primarily through left ventricular (LV) compression. However, achieving optimal compression without direct visualization can be challenging. Point of care transesophageal echocardiography (TEE) serves as an invaluable tool for real-time guidance, ensuring accurate chest compression positioning over the LV apex. In this case, initial compressions were misaligned over the left ventricular outflow tract (LVOT) and aortic valve (AV). TEE assessment enabled real-time identification and precise repositioning of compressions to the LV apex, resulting in marked improvements in arterial pressure waveforms and end-tidal CO2 (ETCO2)—both reliable indicators of CPR quality. This case highlights the critical role of TEE in cardiac arrest management, offering real-time diagnostic insights and optimizing compression mechanics. Integrating TEE into resuscitation protocols enhances the quality of chest compressions, supports hemodynamic stability, and may ultimately improve patient outcomes.